“Dried Flowers”. A comic picture of education in Polish popular literature of the 19th century and the culture of laughter at that time - Grzybowski, Przemysław Paweł (Laughter, humour, satire, 2024)
This article presents a research report on comic content related to education in Polish popular literature of the 19th century. This content concerns both the family environment and the element of the public education system. Based on the analysis of the content of 47 literary works, the author indicates the most important personal patterns and comic threads related to education. It presents them against the backdrop of the contemporary culture of laughter and the circumstances of the reception of comic.